Online peer engagement in adolescence: Positive and negative aspects of online social interaction - Monks,CP; Van,Zalk N (2020)
This book provides an in-depth insight into what is currently known and relatively unknown about youths' online peer engagement. It delivers state-of-the-art current reviews of the literature in the field, with a strong coverage of methodological issues in studying online friendships and an emphasis on moving towards a new, less dichotomic, view of online peer interaction in adolescence. With a focus on what spending time with online-exclusive peers entails - in terms of both potential positive as well as negative consequences for friendship quality, intimacy, and well-being - this book offers a more nuanced commentary on youths' online peer engagement. Including coverage of the evolution of online friendships, cyberbullying, cyberdating, sexting, online abuse, smartphones, social networks, as well as their impact on adolescent social interaction online, Van Zalk and Monks consider implications for future research directions and practical applications. Online Peer Engagement in Adolescence is important reading for undergraduate and master students studying social and developmental psychology, education, relationships and health, as well as advanced researchers and academics working in these fields.